2021
DOI: 10.1186/s40942-021-00307-7
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of sterile inflammation after intravitreal injection of antiangiogenic drugs: a narrative review

Abstract: Background Intraocular inflammation is an uncommon but potentially vision-threatening adverse event related to anti-VEGF therapy. This is of increasing importance given both the volume of injections performed, as well as the increased prevalence of inflammation seen with newer anti-VEGF agents. Brolucizumab, the newest anti-VEGF agent, has been associated with an inflammatory retinal vasculitis and the underlying mechanism is unclear. Reviewing potential mechanisms and clinical differences of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
74
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(81 citation statements)
references
References 82 publications
2
74
0
5
Order By: Relevance
“…After the first brolucizumab injection, it took as long as 8 weeks (range: 2 to 8 weeks) after for retinal vasculitis, which in this series was typically occlusive and could involve the retinal arteries, veins, and potentially capillaries with a range of severity, to be diagnosed. [9][10][11][12][13][14] These real-world reports reflect the results of the phase III HAWK and HARRIER trial mentioned previously. It was concluded that brolucizumab was generally well received, and as a whole, the AE rates paralleled those with aflibercept within each trial.…”
Section: Introductionsupporting
confidence: 80%
See 1 more Smart Citation
“…After the first brolucizumab injection, it took as long as 8 weeks (range: 2 to 8 weeks) after for retinal vasculitis, which in this series was typically occlusive and could involve the retinal arteries, veins, and potentially capillaries with a range of severity, to be diagnosed. [9][10][11][12][13][14] These real-world reports reflect the results of the phase III HAWK and HARRIER trial mentioned previously. It was concluded that brolucizumab was generally well received, and as a whole, the AE rates paralleled those with aflibercept within each trial.…”
Section: Introductionsupporting
confidence: 80%
“…In separate studies, clinical cases of retinal vasculitis after brolucizumab 6mg IVI were gathered from retinal specialists across the US. [9][10][11][12][13][14] One real-world, nonconsecutive series reported 15 eyes with retinal vasculitis and IOI after brolucizumab IVI. After the first brolucizumab injection, it took as long as 8 weeks (range: 2 to 8 weeks) after for retinal vasculitis, which in this series was typically occlusive and could involve the retinal arteries, veins, and potentially capillaries with a range of severity, to be diagnosed.…”
Section: Introductionmentioning
confidence: 99%
“…While some cases of sterile endophthalmitis may mimic infectious IRE, others are characterized by a milder intraocular inflammation and relatively preserved vision. Symptoms present 1–7 days after the injection with the mean time to presentation in a multi-center study at 2.6 days [ 11 , 14 16 ]. Common symptoms include floaters (60%) and blurred vision (93%) with hypopyon (4%), conjunctival injection (10%), and fibrin (3%) occurring significantly less often than in infectious endophthalmitis (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Various factors have been suggested to explain sterile IRE post anti-VEGF injection including patient specific (development of antibodies after repeated exposure, retinal disease related compromise of the blood-retinal barrier, and history of intraocular or systemic inflammatory disease), delivery specific (silicone oil in syringes, syringe agitation, inconsistencies in medication handling), and medication specific (contamination with bacterial endotoxin, medication impurities, formulation, and presence of potentially pro-inflammatory Fc portion of antibody) [ 14 , 16 ]. Clusters of sterile IRE related to breakdowns of the manufacturing process, as was the case in an outbreak due to bacterial endotoxin contamination, have been reported [ 39 ].…”
Section: Resultsmentioning
confidence: 99%
“…Since recognition of this problem, substantial efforts have been undertaken, primarily driven by Novartis, but also by independent experts to understand this phenomenon 4,[7][8][9] and to provide expert guidelines for its treatment. 2,10,11 Real-world evidence gathered from two large us registries (IRIS and Komodo), together covering 21394 injections, indicates that a history of intraocular inflammation or vascular occlusion in the affected eye results in a tenfold increase in the risk of IOI after Brolucizumab from 0.32-0.41% to 3.97-4.68%.…”
mentioning
confidence: 99%